Waste apple biomass conversion to 5-HMF over tin doped sulfonated activated carbon as a catalyst. (January 2023) - Tempelman, Christiaan; Jacobs, Urjan; Herselman, Jan; van Driel, Ruben; Schraa, Feiko; Versijde, Joshua; van Waversveld, Tristan; Yagci, Yasin; Barg, Micky; Smits, Frank; Kuijpers, Femke; Lamers, Kim; et al.
Abstract: Utilisation of lignocellulosic agricultural waste biomass could provide a carbon net zero alternative for production of valuable chemicals. However, the progress is hindered because there's no catalyst to carry out a selective and efficient conversion process. In this study a new promising catalyst for this challenging conversion is reported. It is prepared by sulfonation of activated carbon followed by the impregnation of tin (Sn). The catalyst has been characterized by NH3 -TPD, FTIR, XRF and N2 physisorption. The catalyst was tested at 120 °C for the conversion of model carbohydrate mixtures prepared in the laboratory and real biomass mixtures of apple fruit biomass waste. The catalytic performance for the conversion of a model carbohydrate mixture resulted in a 5-hydroxymethylfurfural (5-HMF) yield of 30% in 80 min. On the other hand, catalytic testing of real apple pomace biomass showed a 5-HMF yield of 24% in 80 min. The Sn catalyst was also shown to maintain the 5-HMF yield in recycle experiments using a model carbohydrate mixture. Conversely, stability was lower when the Sn catalyst was tested in real apple pomace mixture, which is likely due to the presence of other impurities. Highlights: Low temperature (120 °C) conversion of carbohydrates rich agricultural apple fruit waste to 5-HMF. Cheap and easy method for the preparation of tin doped sulfonated carbon catalysts. Characterization revealed that the Sn-Fn-Ac catalyst contained both Lewis and Brønsted acidity. Sn-Fn-AC showed for glucose, fructose and sucrose mixtures 30% 5-HMF yield at conversion of 60%. Catalytic conversion of carbohydrate mixtures from biomass yielded 24% of 5-HMF respectively.